Into the White: Larry Eigner’s Meta-Physical Poetics - Lauro, Sarah Juliet; Riordan, Lindsay Waggoner (Disability Studies Quarterly, 2014)
Disabled poet Larry Eigner makes striking use of the space of the page to create poetry that operates in a visual as well as linguistic register. Many critics have read Eigner’s oeuvre in light of his physical condition, but no scholar has previously looked to the parallels between the Black Mountain artists’ experiments in abstraction and Black Mountain poet Larry Eigner’s work, though the same influences are clearly evident. Working collaboratively and interdisciplinarily, the authors combine their expertise in the disciplines of literature and art history, reading both the words on the page and the page as picture, in a manner that engages specifically with phenomenological philosophy, to explicate how these poems work on the body of the reader. Key words: embodiment, abstraction, poetics, typography, metaphysics, phenomenology